2003
DOI: 10.1097/00126334-200306010-00012
|View full text |Cite
|
Sign up to set email alerts
|

Viagra Use in a Community-Recruited Sample of Men Who Have Sex With Men, San Francisco

Abstract: The authors conducted a community-based anonymous survey of 837 men who have sex with men (MSM) to gauge the extent of Viagra (sildenafil citrate) use, its association with high-risk sexual behavior, and its combination with other drugs. Participants' mean age was 35 years, 67% were white, and 66% had a college degree. The majority (76%) reported anal sex in the past 6 months, with 49% reporting always using condoms. Overall, 32% had ever used Viagra (CI: 29%-36%). Significant independent predictors of Viagra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 8 publications
5
61
1
2
Order By: Relevance
“…Although using sildenafil was positively associated with both risky sexual behavior and HIV-positive status, significantly fewer HIV-positive men participated in risky sexual behavior than HIV-negative men. Some studies have reported that risky sex is associated with sildenafil use when sildenafil is combined with club drugs such as ecstasy, methamphetamine, or amyl nitrate to enhance the sexual experience (Chu et al, 2003;Crosby & DiClemente, 2004;Kim et al, 2002). It is possible that the HIV-positive men in this sample were less likely to use sildenafil recreationally than the HIV-negative men.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Although using sildenafil was positively associated with both risky sexual behavior and HIV-positive status, significantly fewer HIV-positive men participated in risky sexual behavior than HIV-negative men. Some studies have reported that risky sex is associated with sildenafil use when sildenafil is combined with club drugs such as ecstasy, methamphetamine, or amyl nitrate to enhance the sexual experience (Chu et al, 2003;Crosby & DiClemente, 2004;Kim et al, 2002). It is possible that the HIV-positive men in this sample were less likely to use sildenafil recreationally than the HIV-negative men.…”
Section: Discussionmentioning
confidence: 88%
“…For example, in a qualitative study of older MSM, erectile dysfunction was related to decreased desire to use condoms (Murray & Adam, 2007). However, sildenafil use allowed some men with erectile dysfunction to increase sexual activity (Murray & Adam, 2007), and several studies have shown that sildenafil use is correlated with HIV infection and risky sexual behavior (Chu et al, 2003;Kim, Kent, & Klausner, 2002;Sanchez & Gallagher, 2006;Sherr, Bolding, Maguire, & Elford, 2000).…”
mentioning
confidence: 99%
“…For example, in a study of MSM attendees of a sex resort in Georgia, Crosby and DiClemente [17] reported that Viagra was more implicated in substance abuse rather than sexual risk behavior. But in a community-based convenience sample of MSM in San Francisco, Chu et al, [18] found a strong relationship between Viagra use and risky sexual behavior as well as a significant association with combined and illicit drug use. This dual result is the more common finding among studies to date.…”
Section: Introductionmentioning
confidence: 95%
“…In a longitudinal study of urban MSM, Koblin and her colleagues (Koblin et al 2006) reported that use of amphetamines nearly doubled a study participant's chance of HIV seroconversion (hazard ratio of 1.96), but use of marijuana, poppers, hallucinogens, or cocaine or crack were not associated with seroconversion in multivariate analyses. Research has highlighted the risk-augmenting roles of other substances among MSM, including amyl nitrates or ''poppers,'' and PDE-5 inhibitors such as Viagra Ò (Chu et al 2003;Kim et al 2002;Loeb 2004;Purcell et al 2005a, b;Paul et al 2005;Romanelli and Smith 2004;Swearingen and Klausner 2005).…”
Section: Introductionmentioning
confidence: 99%